Coccidiosis: recent advancements in the immunobiology of Eimeria species, preventive measures, and the importance of vaccination as a control tool against these Apicomplexan parasites - Shivaramaiah C (Dove Medical Press, 2014)
Chaitanya Shivaramaiah,1 John R Barta,2 Xochitl Hernandez-Velasco,3 Guillermo Téllez,1 Billy M Hargis11Department of Poultry Science, University of Arkansas, Fayetteville, AR, USA; 2Department of Pathobiology, University of Guelph, ON, Canada; 3Facultad de Medicina Veterinaria y Zootecnia, Universidad Nacional Autonoma de Mexico, MexicoAbstract: Coccidiosis, caused by parasites of the genus Eimeria, is probably the most expensive parasitic disease of poultry. Species of Eimeria are ubiquitous where poultry are raised and are known to cause drastic reductions in performance and induce mortality, thereby affecting the overall health status of poultry. Chemotherapy has been the predominant form of disease control for many years, even though vaccination is steadily gaining importance as a feasible control method. The objective of this review is to highlight recent advancements in understanding the role of host immunity against coccidiosis. In addition, pros and cons associated with chemotherapy and the role of vaccination as an increasingly popular disease control method are discussed. Finally, the role played by recombinant vaccines as a potential vaccination tool is highlighted. With interest growing rapidly in understanding host–parasite biology, recent developments in designing recombinant vaccines and potential epitopes that have shown promise are mentioned.Keywords: Eimeria, coccidiosis, chemotherapy, recombinant vaccines, immunity